2014
DOI: 10.1111/anec.12145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inhomogeneities of Repolarization in Patients with Systemic Lupus Erythematosus

Abstract: Our study revealed that QTd, cQTd, Tp-e interval and Tp-e/QT ratio increased in patients with SLE. Also, Tp-e interval and Tp-e/QT were positively correlated with disease duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Studies performed to date have demonstrated increased rates of Tp-e interval and Tp-e/QT in autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, and ankylosing spondylitis, exhibiting an intense systemic inflammation response. In addition, this increase was detected to be correlated with inflammatory parameters [3537]. Some authors underlined the fact that this electrical abnormality could be a predictor of potential cardiac arrhythmias and cause predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed to date have demonstrated increased rates of Tp-e interval and Tp-e/QT in autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, and ankylosing spondylitis, exhibiting an intense systemic inflammation response. In addition, this increase was detected to be correlated with inflammatory parameters [3537]. Some authors underlined the fact that this electrical abnormality could be a predictor of potential cardiac arrhythmias and cause predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Tpe interval in precordial leads, its dispersion and its ratio with QT in V5 have been suggested to provide an indirect and non‐invasive assessment of repolarisation heterogeneity, and they have been evaluated in many cardiac and systemic diseases such as Brugada syndrome, long and short QT syndrome, hypertrophic cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, coronary heart disease, heart failure, hypertension, diabetes mellitus, systemic lupus erythematosus and ankylosing spondylitis …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the Tp-Te interval was prolonged in patients with rheumatoid arthritis and systemic lupus erythematosus. 32 , 37 In another study, Akcay et al 6 reported that the Tp-Te interval was increased in FMF patients. Similar to that study, we found that the Tp-Te interval was statistically significantly prolonged in FMF patients.…”
Section: Discussionmentioning
confidence: 98%
“… 35 , 36 Previous studies have shown that QTd was significantly higher in some inflammatory diseases. 32 , 37 …”
Section: Discussionmentioning
confidence: 99%